Occurrence of prophage and historical perspectives associated with the dissemination of huanglongbing in mainland China. (13th October 2019) - Fu, S.; Bai, Z.; Su, H.; Liu, J.; Hartung, J. S.; Zhou, C.; Wang, X.
Abstract : Huanglongbing (HLB), associated with a non‐culturable bacterium ' Candidatus Liberibacter asiaticus' (CLas), is a highly destructive citrus disease with a long but poorly documented history in China. No effective treatment for HLB is available. The identification of new prophages in abundant CLas genomic sequence data provides new insights into both the diversity of CLas strains and HLB management. In this study, CLas populations from nine provinces were surveyed for the presence of prophage. Two major prophage typing groups (PTGs) were discovered to be associated with two different altitude regions: strains of CLas in PTG1 from high altitude regions (HAR) mainly contained prophage Type 1 only or Types 1 and 3, whereas strains of CLas in PTG2 from low altitude regions (LAR) mainly contained prophage Type 2. The discovery of these CLas population patterns provides evidence for independent origins of HLB in HAR and LAR. Guangdong province is the generally recognized domestic region of origin for HLB and is primarily responsible for the dissemination of HLB in LAR through transport of seedlings. Both Yunnan and Sichuan provinces are the probable regions of origin for HLB in HAR. PTG2 was further divided into two subgroups: PTG2‐1, found in Guangdong, Fujian and Guangxi and PTG2‐2, found in Jiangxi, Zhejiang and Hunan. These regions and prophage types are correlated with early and late introductions of HLB in LAR. These molecular analyses were supported by studying the history of the dissemination of HLB in historical documents.